Incorporating genomic medicine into primary‐level health care for chronic non‐communicable diseases in Mexico: A qualitative study. (1st September 2020) - Bravo, María L.; Santiago‐Angelino, Tania M.; González‐Robledo, Luz M.; Nigenda, Gustavo; Seiglie, Jacqueline A.; Serván‐Mori, Edson
Summary: Objective: To analyze the viability of incorporating genomic medicine technology into the process of detecting and diagnosing chronic non‐communicable diseases (CNCDs) at primary‐care facilities in Mexico, and to discuss its implications for health systems in other countries with similar characteristics. Material and methods: We conducted 29 semi‐structured interviews with health authorities as well as providers and users of health services in the state of Morelos. We investigated knowledge of genomic technology among interviewees; the accessibility, management, and organization of health services; and CNCDs prevention, control, and care practices. Results: The incorporation of genomic medicine technology into the CNCDs primary‐care process is viable. However, the following challenges were identified: a lack of knowledge and limited information among interviewees regarding the effectiveness and benefits of genomic medicine technology, coupled with the need to mobilize and reassign trained human resources for drawing, registering, safeguarding, transporting, and controlling the quality of the genetic samples, as well as for the outsourcing of private laboratory services. Conclusion: Using genetic information to detect CNCDs at an early stage offers an enormous potential for upgrading CNCDs prevention and control efforts. This, in turn, could translate into more efficient and financially sustainable health systems in Mexico and other low‐ and middle‐income countries.